Investigation of Listeria monocytogenes in Meat of Broilers at The Northwestern Region of Syria - Alrahil, AlaaAldin Sobaia; Al-Daoud, Fouad Hamad (Journal of agricultural, environmental and veterinary sciences, 2025)
Listeria monocytogenes is considered one of the most important foodborne pathogens and poses a threat to public health due to its ability to survive in harsh environmental conditions such as refrigeration and high salinity, in addition to its particular danger to immunocompromised groups. This study aimed to investigate the prevalence of L. monocytogenes in marketed broiler meat in Idlib city - northwestern Syria, and to detect other associated species of Listeria spp. and Enterococcus spp., in addition to evaluating the health risks associated with them. (102) samples of broiler meat offered for retail sale were collected and subjected to bacteriological examinations using culture on selective media (Oxford agar), microscopic examination, biochemical tests, and identification using the Vitek-2 device. The results showed the presence of Listeria spp. in (8/102) samples, representing (7.84%). L. monocytogenes was detected in two samples (1.96%), while L. innocua was the most common (five samples, 4.90%), in addition to one L. welshimeri sample (0.98%). Enterococcus faecalis was also detected in two samples (1.96%), suggesting the possibility of mixed contamination. These results suggest that broiler meat may be a potential source of food contamination in the region, calling for enhanced health control and the implementation of good handling and storage practices.
Keywords: Listeria monocytogenes; Listeria spp; broiler meat; Vitek-2; Idlib